Museu e suas tipologias: o webmuseu em destaque - Da Costa Santos, Plácida Leopoldina Ventura Amorim [UNESP] (2014)
The rapid development of Information and Communication Technologies - TIC, coupled with the advancement of the global Internet computer network have framed new concepts and definitions such as virtual reality, immersive environments, webmuseums, digital museums, electronic art, cyber art, among other terminologies that are becoming more and more common and are present in everyday Web users. To better understand the terminologies used to describe museum in the virtual environment, we present a summarized table of terms such as webmuseum, virtual museum, digital museum and their derivatives in order to define the elements that differentiate or resemble them. We used the bibliographic descriptive method for identifying the concepts presented by some expert authors in the field. In conclusion, we recommend the use of the term webmuseum for museums in cyberspace as the most appropriate and we define the concept, comprehending its meaning and characteristics.